Stress Analysis of Buried Pipeline Using Finite Element Method (Journal of University of Babylon for Engineering Sciences, 2019)
This study aims to analyze the behavior of underground part of steel pipelines under the effect of loads caused by internal pressure and temperature variation due to transportation of hydrocarbon products. The pipeline assumed to be buried in a sandy soil. The finite element method is used to carry out this analysis using ANSYS 12.0 program.  Four parameters are studied including length of the buried part of the pipeline, soil properties, depth of soil cover, and ends condition of the buried part of the pipeline. It is found that increasing the length of the buried part of the pipeline or increasing values of the normal and tangential modulus of subgrade reactions for the surrounding soil causes decreasing in the values of longitudinal displacement, stress, and strain. Soil cover depth over buried pipeline has no effect on the longitudinal displacement, but the stresses and strain increased when the soil cover depth increases. From studying the effect of boundary conditions of the two ends of steel buried pipeline, it is found that longitudinal maximum displacement did not affected, but the longitudinal stresses and strains increase with small rate values.